Testing, Analysis and Classification of No-Dig Manhole Rehabilitation Materials - Kaushal, Vinayak; Najafi, Mohammad; Entezarmahdi, Alimohammad (Frontiers in Water, 2021)
Gravity flow wastewater collection systems are comprised of sewer pipes and manholes. Failure of a manhole may have catastrophic consequences such as developing a sinkhole in the street and roadway, and at a minimum, wastewater flow will be blocked, and stream of the manhole will backup causing a sanitary sewer overflow (SSO). Improving structural conditions of a manhole is critical to minimize these types of failures. This paper considers the impact of several lining materials including cement mortar, epoxy, polyurethane, cured-in-place composites, and a multi-layer structure material on increasing the structural capabilities of deteriorated manholes. The tasks included in this research consist literature search and, preliminary laboratory and main testing of select manhole rehabilitation materials. A finite element analysis is included to complement the experiments. Several preliminary tests according to ASTM C-39 on coated concrete cylinders, and ASTM C-293 on lined concrete beams, were performed at UT Arlington's Center for Underground Infrastructure Research and Education (CUIRE) Laboratory. The test results showed significant increase in the performance of concrete samples under compression and flexure. A second round of testing was performed on 4-ft long, 24-in. diameter concrete pipe sections with 3-in. wall thickness manufactured according to ASTM C-76. These pipe sections were lined internally with the same materials as the preliminary tests, and tested according to ASTM C-497 under Three-Edge-Bearing testing. Using computer data acquisition system, strain gages and displacement extensometers, stress/strain data were measured. The results showed that tested No-Dig manhole rehabilitation materials can significantly improve structural performance of deteriorated manholes.